The Effect of Coal Production, Profitability, Leverage, Newcastle Price on Firm Value with Renewable Energy Moderation - Sihombing, Pardomuan; Priambhodo, Yohanes Dimas (SAN Scientific, 2024)
The flow of investment funds from global fund managers to energy sector stocks is increasing and is focused on renewable energy. Regarding this, several energy sector companies in Indonesia have started to diversify their business into renewable energy. This research uses panel data analysis, which aims to see the influence of various variables, including coal production, profitability, leverage, and Newcastle coal price with renewable energy as a moderator on the value of energy sector companies. The companies in the sample are the coal sub-sector energy sector listed on the Indonesia Stock Exchange in 2018-2022. The results of this research show that profitability has a positive influence on firm value. For coal production, leverage and Newcastle coal prices do not affect firm value. Apart from that, renewable energy is also unable to moderate the influence of coal production, leverage, and Newcastle coal price on Firm value. The managerial implication of this research is that companies in the energy sector need to pay attention not only to traditional factors such as coal production, profitability, and leverage but also to new factors such as Newcastle coal prices and renewable energy as moderators.